2017
DOI: 10.1021/acs.biochem.7b00047
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction and Design for Creating Iteratively Larger Heterospecific Coiled Coil Sets

Abstract: A major biochemical goal is the ability to mimic nature in engineering highly specific protein-protein interactions (PPIs). We previously devised a computational interactome screen to identify eight peptides that form four heterospecific dimers despite 32 potential off-targets. To expand the speed and utility of our approach and the PPI toolkit, we have developed new software to derive much larger heterospecific sets (≥24 peptides) while directing against antiparallel off-targets. It works by predicting T valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…As a result, they are increasingly used as templates for protein design and sequences with a pre-determined thermodynamic stability can now be synthesized de novo. [3][4][5][6] Such sequences find application in peptide-based hydrogels [7][8][9][10] and protein origami structures 11,12 as well as in biosensors 13 and drug delivery systems. 8,[14][15] Considering their natural role as a mechanical scaffold, surprisingly little information is available about the sequence-structure-mechanics relationship of CCs.…”
Section: Figure 1 Experimental Design A) CC Heptad Pattern B) Smfsmentioning
confidence: 99%
“…As a result, they are increasingly used as templates for protein design and sequences with a pre-determined thermodynamic stability can now be synthesized de novo. [3][4][5][6] Such sequences find application in peptide-based hydrogels [7][8][9][10] and protein origami structures 11,12 as well as in biosensors 13 and drug delivery systems. 8,[14][15] Considering their natural role as a mechanical scaffold, surprisingly little information is available about the sequence-structure-mechanics relationship of CCs.…”
Section: Figure 1 Experimental Design A) CC Heptad Pattern B) Smfsmentioning
confidence: 99%
“…As a result, they are increasingly used as templates for protein design and sequences with a pre-determined thermodynamic stability can now be synthesized de novo. [5][6][7][8] Such sequences find application in peptide-based hydrogels [9][10][11] and protein origami structures 12,13 as well as in biosensors 14 and drug delivery systems. 15 Considering their natural role as a mechanical scaffold, surprisingly little information is available about the sequence-structuremechanics relationship of CCs.…”
mentioning
confidence: 99%
“…Recently, Crooks et al developed the largest CC set so far. 52 Using the bCIPA algorithm 53 a set of 8 parallel heterodimers was constructed comprising 4 heptad repeats. However, T m measurements revealed that only 7 pairs behaved as designed with T m 4 70 1C and at least a 10 1C gap before the most stable off-target interaction.…”
Section: Orthogonal Coiled Coil Setsmentioning
confidence: 99%
“…Firstly, the explored sequence space is restrained in accordance with previous rules discovered to govern CC oligomerization and pairing specificity. In the previously mentioned examples concerning the design of parallel CC sets, 47,48,52 only lysine and glutamic acid were allowed at e:g positions, while the a heptad positions could be occupied either by asparagine or isoleucine and at d positions only leucine was allowed. Only a, d, e and g heptad positions were subjected to design, while b, c, and f positions were occupied by helicity promoting amino acids.…”
Section: Orthogonal Coiled Coil Setsmentioning
confidence: 99%